Dialectical theology and Jacques Ellul : an introductory exposition - Van Vleet, Jacob E. (2014)
Jacob E. Van Vleet argues that the work of Jacques Ellul is frequently misread on account of inattention to the theological underpinning that governs Ellul's thought. In a penetrating analysis, the first of its kind, Van Vleet provides a substantive account of the theological structure of Ellul's work and demonstrates the determinative role that theology plays in a proper understanding of Ellul. The book offers a major introduction to Ellul's thought, his contribution to theology and philosophy, and how his philosophy of technology is both theologically informed and culturally relevant.
Introduction -- The skeleton key-dialectical hermeneutics -- Primary Influences on Ellul's Dialectical Worldview -- Ellul's Dialectical Worldview -- God, Salvation, and Freedom -- Technique, Necessity, and Consequences -- Propaganda and Politics -- Hope, NonViolence, and Christian Anarchism -- Conclusion -- Jacques Ellul-dialetician and prophet.
Includes bibliographical references and index.
Keywords: Ellul, Jacques, -- 1912-1994 -- Religion; Dialectical theology